Comparative Study of the Kinetic Properties of Proton and Alpha Beams in the Alfvénic Wind Observed by SWA-PAS On Board Solar Orbiter - Roberto Bruno; Rossana De Marco; Raffaella D’Amicis; Denise Perrone; Maria Federica Marcucci; Daniele Telloni; Raffaele Marino; Luca Sorriso-Valvo; Vito Fortunato; Gennaro Mele; Francesco Monti; Andrei Fedorov; et al. (The Astrophysical Journal, 2024)
The problems of heating and acceleration of solar wind particles are of significant and enduring interest in astrophysics. The interactions between waves and particles are crucial in determining the distributions of proton and alpha particles, resulting in non-Maxwellian characteristics, including temperature anisotropies and particle beams. These processes can be better understood as long as the beam can be separated from the core for the two major components of the solar wind. We utilized an alternative numerical approach that leverages the clustering technique employed in machine learning to differentiate the primary populations within the velocity distribution rather than employing the conventional bi-Maxwellian fitting method. Separation of the core and beam revealed new features for protons and alphas. We estimated that the total temperature of the two beams was slightly higher than that of their respective cores, and the temperature anisotropy for the cores and beams was larger than 1. We concluded that the temperature ratio between alphas and protons largely over 4 is due to the presence of a massive alpha beam, which is approximately 50% of the alpha core. We provided evidence that the alpha core and beam populations are sensitive to Alfvénic fluctuations and the surfing effect found in the literature can be recovered only when considering the core and beam as a single population. Several similarities between proton and alpha beams would suggest a common and local generation mechanism not shared with the alpha core, which may not have necessarily been accelerated and heated locally.